The Implementation and Food Safety Issues Associated With Poultry Processing Reuse Water for Conventional Poultry Production Systems in the United States - Micciche, Andrew C.; Feye, Kristinia M.; Rubinelli, Peter M.; Wages, Jennifer A.; Knueven, Carl J.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2018)
As human populations increase in numbers, access to clean, fresh water is becoming increasingly difficult to balance between agricultural and municipal demands. Water scarcity is a limiting factor of food production in many countries, whether they are emerging or established economies. In conventional poultry processing systems, access to water is particularly critical for the maintenance and disinfection of processing areas, as well as in processing operations such as scalding, chilling, and carcass washing. Therefore, poultry processing plants use an excessive amount of water, limiting where facilities can operate, increasing overhead costs, and ultimately resulting in potential environmental concerns. The need for sustainable alternatives to single-use water supplies is becoming increasingly more urgent. As a result, the implementation of water reuse in poultry-processing plants has emerged as an attractive alternative means to meet water requirements during processing. Because the water is reused, it is essential to de-contaminate the water with chemicals, such as peracetic acid and chlorine, and improve water filtration strategies to kill and remove potential pathogens and contaminants. However, questions remain as to the efficacy of commonly used disinfectants to achieve that goal. Thus, novel strategies must be developed to improve the capabilities of poultry processing plants to counter water insecurity worldwide. These new stratagems must be economical and enable poultry processing plants to reduce their environmental footprint while meeting new food safety challenges. The current review will focus exclusively on water reuse in conventional poultry processing in the United States. The specific objectives of this review are to discuss the approaches for treating processing water in poultry processing systems, including reuse water systems, as well as investigate possible substitutes for maintaining food safety.